2012
DOI: 10.1063/1.4754127
|View full text |Cite
|
Sign up to set email alerts
|

Angle-resolved environmental X-ray photoelectron spectroscopy: A new laboratory setup for photoemission studies at pressures up to 0.4 Torr

Abstract: . (2012). Angle-resolved environmental X-ray photoelectron spectroscopy: A new laboratory setup for photoemission studies at pressures up to 0.4 Torr. Review of Scientific Instruments, 83(9) The paper presents the development and demonstrates the capabilities of a new laboratory-based environmental X-ray photoelectron spectroscopy system incorporating an electrostatic lens and able to acquire spectra up to 0.4 Torr. The incorporation of a two-dimensional detector provides imaging capabilities and allows the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 25 publications
4
35
0
Order By: Relevance
“…X-ray photoelectron spectroscopy (XPS) is a powerful surface characterisation technique, providing insightful information about the elements present on a given surface, including their respective chemical states and concentrations across as many as a few tens of atomic layers. However, the short mean-free path of electrons with energies below 1500 eV in a gas at ambient pressure does not allow XPS analyses to be performed under realistic experimental conditions, from an applications point of view, 7 and a vacuum level is required for X-ray anodes and channeltrons. These problems can be partly overcome by performing socalled "environmental," "ambient-pressure," or "high-pressure" XPS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…X-ray photoelectron spectroscopy (XPS) is a powerful surface characterisation technique, providing insightful information about the elements present on a given surface, including their respective chemical states and concentrations across as many as a few tens of atomic layers. However, the short mean-free path of electrons with energies below 1500 eV in a gas at ambient pressure does not allow XPS analyses to be performed under realistic experimental conditions, from an applications point of view, 7 and a vacuum level is required for X-ray anodes and channeltrons. These problems can be partly overcome by performing socalled "environmental," "ambient-pressure," or "high-pressure" XPS.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Nonetheless, these techniques suffer from drawbacks, such as reduced energy resolution and specimen freedom of movement, high cost, and accessibility to the facilities, as most of them are dedicated for operation at synchrotron light sources. Some laboratory-scale solutions have also been developed recently, 7,11,12 allowing for environmental XPS analyses to be performed with a reduced cost and increased availability. Unfortunately, it has to be concluded that the so-called "pressure gap" in XPS can still only be partially filled with a limited maximum pressure, lower spectrometer resolution, and high cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AP-PES dates back to the efforts of Siegbahn and co-workers in the 1970s [19][20][21]. The technique has developed rapidly in recent years due to the use of differentially pumped electron lens systems in both synchrotron-based [22][23][24][25][26] and laboratory-based systems [27,28]. One of the main challenges of AP-PES techniques is the scattering of the photoemitted electrons by the ambient gas phase molecules when the pressure is increased.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Further designs were based on a "wetted wire" 5 or a rotating metal disk 6 for transporting the liquid into the analysis chamber. The majority of today's typical high-pressure photoelectron spectrometers are designed primarily for the study of solid surfaces under a high pressure (HP) gas atmosphere, and incorporate a small-volume "high-pressure" cell 7 or a backfilled analysis chamber 8 as described in more detail in Ref. 9.…”
Section: Introductionmentioning
confidence: 99%